Signals in Science - On the Importance of Signaling in Gaining Attention in Science - Hendrik P. van Dalen; Kène Henkens (Tinbergen Institute, 2004)
Which signals are important in gaining attention in science? For a group of 1,371 scientific articles published in 17 demography journals in the years 1990-1992 we track their influence and discern which signals are important in receiving citations. Three types of signals are examined: the author's reputation (as producer of the idea), the journal (as the broker of the idea), and the state of uncitedness (as an indication of the assessment by the scientific community of an idea). The empirical analysis points out that, first, the reputation of journals plays an overriding role in gaining attention in science. Second, in contrast to common wisdom, the state of uncitedness does not affect the future probability of being cited. And third, the reputation of a journal may help to get late recognition (so-called `sleeping beauties') as well as generate so-called `flash-in-the-pans': immediately noted articles but apparently not very influential in the long run.
Keywords: C41; D83; O31; O33; 330; signaling; duration dependence; journals; impact; citations; Bibliometrie; Signalling; Reputation